Reaching the unheard: multistakeholder dialogues towards resilient landscape management planning in West Africa - Atampugre, Gerald; Oke, Adebayo; Igbadun, H. E.; Tilahun, Seifu A.; Cofie, Olufunke O.; Mabhaudhi, Tafadzwanashe (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2023)
Multistakeholder dialogues are crucial in breaking down silos and bringing together diverse voices across landscapes. These dialogues ensure that everyone's needs are considered, leading to fairer and more inclusive outcomes. In the context of the CGIAR Initiative on Transforming AgriFood Systems West and Central Africa (TAFS-WCA), several MSDs were organized in targeted landscapes in Ghana and Nigeria to co-develop inclusive landscape management plans (ILMPs). The MSDs assessed the status and dynamics of natural resources and ecosystem services, validated the LSA findings, and aided knowledge-sharing, partnership-building, and community mobilization for sustainable and resilient landscapes. The approach to the MSDs in both countries was guided by a combination of collaborative and empowerment engagement methods like focus groups, partnership building, and community mobilization. The principles of a successful MSD include inclusiveness, transparency, respect, facilitation, and decision-making. All relevant stakeholders were invited to participate, regardless of their background or position. The MSDs in Ghana validated most of the LSA results, with new information on drivers of change, state, and dynamics of natural resource use in the target social-ecological landscape. Participants came with new information including disunity between farmers and miners, changes in family practices, increased postharvest losses, reduced food production, new diseases, illegal mining due to new technology, and the inappropriateness of Cinderella Trees for agroforestry. In the Doma-Rutu productive landscape, MSDs confirmed that dwindling water resources affect agricultural productivity, floods in rice fields around the Ohina River, and common livelihood activities among women contributing to forest degradation and stream siltation. The State government proposed Operation Green Nasarawa State, which networks with charcoal producers, firewood traders, tree loggers, and timber traders. By reflecting on the experiences, valuable lessons were learned that could improve future MSDs: • The importance of long-term commitment: Building trust and achieving lasting results requires long-term commitment from all stakeholders. • The need for flexibility: The process could have been more flexible to adapt to changing circumstances and emerging needs before and during the MSDs. • The value of continuous learning: Dialogue participants and facilitators/researchers could have been more open to learning from each other. Finally, the process gave an opportunity within this mobilization effort to identify citizen scientists, especially in Ghana. The aim was to involve residents in gathering water quality and quantity data and engage them in the MSD. This approach highlights a creative and inclusive method to collect valuable information and reach back to the community for an inclusive landscape management plan.